2005
DOI: 10.1121/1.1828474
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of mature gestural patterns in the production of voiceless and voiced word-final stops

Abstract: The organization of gestures was examined in children's and adults' samples of consonant-vowel-stop words differing in stop voicing. Children (5 and 7 years old) and adults produced words from five voiceless/voiced pairs, five times each in isolation and in sentences. Acoustic measurements were made of vocalic duration, and of the first and second formants at syllable center and voicing offset. The predicted acoustic correlates of syllable-final voicing were observed across speakers: vocalic segments were shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 33 publications
3
16
0
Order By: Relevance
“…As expected, we found statistically significant increases in rates of diadochokinesis, second formant transitions, and standard syllabic rates with increasing age. The results from these voice and articulation parameters are consistent with numerous studies in the literature that demonstrate improved control of articulation with increasing age in children [8,9]. In 2008, Singh and Singh performed spectral-temporal analyses of syllabilicity, formant transitions, and place of articulation in 155 children between 4 and 8 years, with an equal number of boys and girls.…”
Section: Discussionsupporting
confidence: 85%
“…As expected, we found statistically significant increases in rates of diadochokinesis, second formant transitions, and standard syllabic rates with increasing age. The results from these voice and articulation parameters are consistent with numerous studies in the literature that demonstrate improved control of articulation with increasing age in children [8,9]. In 2008, Singh and Singh performed spectral-temporal analyses of syllabilicity, formant transitions, and place of articulation in 155 children between 4 and 8 years, with an equal number of boys and girls.…”
Section: Discussionsupporting
confidence: 85%
“…These results support hypothesis 4 and agree with previous studies (e.g., Kent and Forner, 1980;Sharkey and Folkins, 1985;Nittrouer, 1993;Smith and Goffman, 1998;Lee et al, 1999;Nijland et al, 2002;Walsh and Smith, 2002;Nittrouer et al, 2005;Zharkova et al, 2011Zharkova et al, , 2012. The results were statistically significant for both measures of tongue shape in both vowel contexts.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies have demonstrated developmental decreases in variability in durational and spectral measures (e.g., Kent and Forner, 1980;Nittrouer, 1993;Lee et al, 1999;Nijland et al, 2002;Nittrouer et al, 2005), labial and mandibular articulation (e.g., Sharkey and Folkins, 1985;Smith and Goffman, 1998;Walsh and Smith, 2002), as well as lingual articulation (e.g., Zharkova et al, 2011Zharkova et al, , 2012Barbier et al, 2015;Yip et al, 2015). This study for the first time described age-related changes in variability of tongue shape over repetitions of the same speech segment, in subjects between 3 and 13 years old.…”
Section: Variabilitymentioning
confidence: 99%
“…Natural-formant-The natural-formant stimuli were based on natural tokens of an adult, male speaker producing the words buck and bug in isolation. Nittrouer et al (2005) provide complete results of acoustic analyses on these and similar words, and measures from that study served as a guide for creating these stimuli. In both kinds of stimuli, F3 was held constant at 2700 Hz until 50 ms before offset.…”
Section: Stimulimentioning
confidence: 99%